Cost-Effectiveness of Comprehensive School Reform in Low Achieving Schools - Ross, John A.; Scott, Garth; Sibbald, Tim M. (Alberta Journal of Educational Research, 2012)
We evaluated the cost-effectiveness of Struggling Schools, a user-generated approach to Comprehensive School Reform implemented in 100 low achieving schools serving disadvantaged students in a Canadian province. The results show that while Struggling Schools had a statistically significant positive effect on Grade 3 Reading achievement, d=.48 in 2005-06 and .60 in 2006-07, the program was not cost-effective when compared to two alternatives: 1. The cost of bringing one student to the provincial achievement standard was more than 25% higher in Struggling Schools than in the status quo. 2. The cost-effectiveness ratio (i.e., effect size per $1,000 of incremental cost) was lower in Struggling Schools than in Success For All. Struggling Schools would have been deemed to be cost-effective if different choices had been made, especially in (a) the calculation of costs (e.g., the inclusion of donated time), (b) the decision rules for declaring cost-effectiveness, and (c) the studies used to access comparative data. --- Nous avons évalué le rapport cout-efficacité du programme Struggling Schools (écoles en difficulté), une approche générée par l'utilisateur à la réforme d'ensemble des écoles mise en œuvre dans 100 écoles peu performantes desservant des élèves défavorisés dans une province canadienne. Les résultats indiquent que si l'effet du programme Struggling Schools sur le rendement en lecture en 3e année était statistiquement significatif et positif (d= 0,48 en 2005-06 et 0,60 en 2006-07), son rapport cout-efficacité n'était pas aussi intéressant que celui des deux alternatives suivantes: 1. Le cout de rehausser le rendement d'un élève pour qu'il atteigne le standard provincial était plus élevé de 25% avec Struggling Schools par rapport au statut quo. 2. Le rapport cout-efficacité (c.-à-d. l'effet par 1 000$ de cout différentiel) du programme Struggling Schools était plus bas que celui du programme Success for All. Le programme Struggling Schools aurait été jugé rentable si on avait choisi autrement, notamment par rapport (a) au calcul des couts (par ex. l'inclusion de la main d'œuvre à titre gratuit), (b) aux règlements portant sur les décisions quant aux critères de rentabilité, et (c) aux études employées pour accéder aux données de comparaison.